THE EFFECT OF CONCENTRATION OF CAYENNE PEPPER, CURLY CHILI, BIG RED CHILI AND DYEING TIME ON THE QUALITY OF BEEF STORED AT 4°C - Sukasari, Ni Made Chintya Dewi; Swacita, Ida Bagus Ngurah; Rudyanto, Mas Djoko (Buletin Veteriner Udayana; Vol. 14 No. 2 April 2022DO - 10.24843/bulvet.2022.v14.i02.p08, 2022)
Chili is a plant originating from central America and is an important commodity in Indonesian society, some types of chili that are commonly used by Indonesian people include Capsicum frutenscens l. (cayenne pepper), Capsicum annum l. var annum (large chili), and Capsicum anuum l. (curly chili). chili is one of the spices which has compounds that can inhibit pathogenic bacteria or food-destroying bacteria. chili contains a compound from the capsinoid group, capsaicin. capsaicin (8 methyl-n-vanilyl-6-nonenamide) is an active component of chili which produces heat and as an antibacterial in food. this study aims to determine the effect of the concentration of a solution of cayenne pepper, curly chili, large red chili and beef storage quality stored at 4 ° c for a week with a concentration of 25% and 50% in the immersion time for 5, 10, 15 minutes which in terms of pH, water content and water holding capacity. The results found that the type of chili (cayenne, curly, big red) can reduce the water holding capacity and pH and increase the water content of beef stored at 4ºC for a week. The concentration of chili solution (cayenne, curly, big red) can reduce the binding capacity water and pH as well as increasing the water content of beef stored at 4ºC for a week. Length of immersion of beef into chili solution (cayenne, curly, big red) can reduce water holding capacity and pH and increase the water content of beef stored at 4ºC for a week.